STUDENTS’ PERSPECTIVES AND EXPERIENCES ON PROMOTINGREADING INTEREST THROUGH WATTPAD PLATFORM - Nurul Agustina Harahap; Noliza Hasrina (Universitas Samudra, 2023)
STUDENTS’ PERSPECTIVES AND EXPERIENCES ON PROMOTINGREADING INTEREST THROUGH WATTPAD PLATFORM NurulAgustinaHarahap1, Noliza Hasrina1, Fadlia2, Fiza Rauzika Altasa3, AllifSyahputra4. Study Program of English Language Education, Faculty of Teacher Training and Education, Universitas Samudra, Langsa, Indonesia *corresponding author: agustinaharahap10@gmail.com Abstract The aims of this study were to analyze students’ perspectives toward Wattpad on promoting reading and what reading components are affected them by reading Wattpad. A descriptive qualitative method was applied in this study in which questionnaire and interview were employed as the instruments for data collection. This research was conducted at SMA Negeri 1 Langsa, Aceh, where the second grade students were chosen as the participants of this study. The result of the questionnaire showed that all of the students felt that Wattpad was able to promote their reading interest and they also agreed that activities on the platform helped them learn about literature and increased their reading skill. Meanwhile, the result from interview revealed that vocabulary, fluency, and comprehension are the components of reading that were most affected the students by reading Wattpad. Keywords: Reading components, Wattpad, Students’ perspectives